Cloning and expression of the genes specifying Shiga-like toxin production in Escherichia coli H19. - Huang, A (1986)
Some strains of Escherichia coli produce a protein which is cytotoxic for Vero cell and HeLa cell monolayers. This toxin is very similar to the toxin of Shigella dysenteriae 1 and has been named verotoxin or E. coli Shiga-like toxin. It has been shown that toxin conversion is due to a group of bacteriophages, one of which has been designated H-19B. In this study we report hybridization experiments showing that part of the H-19B genome is homologous to phage lambda. We have cloned a 1.7-kilobase BalI-BglII fragment from the genome of H-19B into pUC18. The recombinant plasmid confers the ability to produce high levels of Shiga-like toxin on transformed E. coli cells. We demonstrate using an in vitro transcription/translation system that the cloned fragment specifies the two verotoxin subunit peptides which have masses of 31 and 5.5 kilodaltons. The identity of peptides was confirmed by immunoprecipitation with verotoxin antiserum and protein A-Sepharose beads.